4Pi-RESOLFT nanoscopy - Ulrike Böhm (Nature Portfolio, 2016)
The ability to discriminate objects along the optic axis is a benchmark for three-dimensional imaging techniques. Here, the authors combine metastable-state switching and opposing objective lenses to suppress out-of-focus background and record three-dimensional nanoscale images of living cells.